Determinants of brand love in wine experiences - Dias, Á.; Sousa, B.; Santos, V.; Ramos, P.; Madeira, A. (Wine Economics and Policy, 2024)
Wine tourism provides a multisensory experience through various wine tourism activities. It also adds value to the regions and their producers by enhancing the wine knowledge and sensory experience of the visitors. This study explores the determinants of brand love in wine tourism. Using survey data from wine tourists in Portugal, a structural equation modelling was performed to test the conceptual model. An Importance-performance matrix analysis was also used to obtain additional insights. The results show that the wine tourism enhances brand love. This implies that emotions (i.e., a sense of belonging) towards the overall location is associated with the satisfaction and the quality perception that the winery exhibits. Furthermore, although the consumer’s active participation in wine tourism does not impact brand love directly, its influences occur through the mediating effect of the relation quality. From an interdisciplinary managerial perspective, the present study provides insights into tourism management (i.e., wine tourism) and marketing (i.e., brand management and consumer behaviour).